2013
DOI: 10.1261/rna.040675.113
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of poly(A) site selection in Schizosaccharomyces pombe

Abstract: Polyadenylation of pre-mRNAs, a critical step in eukaryotic gene expression, is mediated by cis elements collectively called the polyadenylation signal. Genome-wide analysis of such polyadenylation signals was missing in fission yeast, even though it is an important model organism. We demonstrate that the canonical AATAAA motif is the most frequent and functional polyadenylation signal in Schizosaccharomyces pombe. Using analysis of RNA-Seq data sets from cells grown under various physiological conditions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 53 publications
5
37
0
Order By: Relevance
“…However, it should be noted that the annotations on the main page represent the longest transcripts observed in one study (Rhind et al 2011), which might not correspond to the most common 5 ′ or 3 ′ UTR. 3 ′ termini determined in a study specifically designed to assess the most frequent site(s) of poly(A) tail addition (Mata 2013) are more reliable and generally agree with another study published around the same time (Schlackow et al 2013); these data can be displayed using the Genome Browser on PomBase. For some genes, UTR length changes during a stress response (Leong et al 2014); these data are not currently available on PomBase but could be added in the future.…”
Section: Mapping Of Mrna Terminisupporting
confidence: 78%
See 1 more Smart Citation
“…However, it should be noted that the annotations on the main page represent the longest transcripts observed in one study (Rhind et al 2011), which might not correspond to the most common 5 ′ or 3 ′ UTR. 3 ′ termini determined in a study specifically designed to assess the most frequent site(s) of poly(A) tail addition (Mata 2013) are more reliable and generally agree with another study published around the same time (Schlackow et al 2013); these data can be displayed using the Genome Browser on PomBase. For some genes, UTR length changes during a stress response (Leong et al 2014); these data are not currently available on PomBase but could be added in the future.…”
Section: Mapping Of Mrna Terminisupporting
confidence: 78%
“…Interest in 3 ′ processing of Pol II transcripts in fission yeast has been stimulated by the discovery of widespread alternative polyadenylation using signals that match the mammalian consensus, in contrast to the more degenerate motifs found in budding yeast (Mata 2013;Schlackow et al 2013). Another key development was the demonstration that this process is regulated (McPheeters et al 2009;Yamanaka et al 2010), at least in part by a poly(A) binding protein present in mammals and fission yeast but absent in budding yeast (St-André et al 2010).…”
mentioning
confidence: 99%
“…S9; data not shown). Our results therefore suggest that the heterogeneity of PAS usage in fission yeast (Mata 2013;Schlackow et al 2013) is not a purely random process but can be modulated by controlling Seb1 levels.…”
Section: Seb1 Controls Poly(a) Site Selectionmentioning
confidence: 75%
“…Recent transcriptome-wide studies indicate that multiple poly(A) sites are used in most eukaryotic genes, as demonstrated in humans (Hoque et al 2013) as well as budding (Ozsolak et al 2010) and fission (Mata 2013;Schlackow et al 2013) yeasts. This process, known as APA, is emerging as a major layer of gene regulation, allowing the inclusion or exclusion of sequences that control the localization, stability, and translation of mRNAs (Tian and Manley 2013).…”
Section: Seb1 Controls Poly(a) Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation